(untitled) (Research, Society and Development, 2021)
This paper aims at reflecting on the experience of constructing a geodesic dome in Elementary Education – based on participants’ memories – to understand elements related to principles of Environmental-Aesthetic Education (EAE) involved in the activity under development. Participants were three students and five teachers who took part in the construction process of the geodesic dome at the Instituto Federal de Ciência e Tecnologia Sul-rio-grandense - Campus Pelotas - Visconde da Graça, located in Pelotas, RS, Brazil. The corpus comprised data collected in semi-structured interviews, field diaries and photographs, which were submitted to Textual Discourse Analysis, proposed by Moraes and Galiazzi. Results show that the construction process of a geodesic dome is a powerful pedagogical and methodological strategy to develop EAE, since it triggers dialogue, participation, collaboration and sharing. Critical reflection, sensitivity development and contact with the natural environment were found in all steps of the process and broadened possibilities of integral education.